Ação da hesperidina em dentina humana submetida a processo erosivo e erosivo/abrasivo: estudo in vitro - Leal, Isabelly de Carvalho (2020)
Dental erosion are being considered a major problem due to its increasing incidence in children and adolescents. Thus, the use of hesperidin (HPN) can present itself as a good approach to control these lesions, since its interaction with dentin promotes cross-links in collagen fibrils, which possibly will hinder the degradation of the organic matrix and increase erosion protection. Therefore, this dissertation aimed to evaluate the action of HPN in diferente concentrations in the protection of the tissue loss in demineralized human dentin by erosion, associated or not to abrasion. This is a randomized in vitro cyclic experiment with 6 experimental groups (n = 10) for erosion (experiment 1) and another 6 groups (n = 10) for erosion associated with abrasion (experiment 2). The treatments were: distilled water (DW) (negative control - without collagenase), DW+Col (negative control - with collagenase), 0.46% EGCG (epigallocatechin-3-gallate) (positive control) and 0.1%, 0.5% or 1% HPN. Collagenase was added in remineralization solution, except for DW-group. The specimens were submitted to erosion cycles with 1% citric acid (5 min), remineralization (60 min), treatment (5 min), abrasion (150 movements) for experiment 2 and remineralization (60 min / overnight). The cycle was repeated 3 times a day for 5 days. Surface changes were evaluated by optical profilometry and scanning electron microscopy. Data were submitted to ANOVA and Tukey test. For experiment 1, DW showed the lowest wear and did not differ significantly from EGCG. DW+Col showed the highest wear and differed significantly from HPN at 1%. In experimente 2, DW showed the lowest wear and DW+Col the highest. EGCG showed less wear than the three groups treated with HPN. There was no significant difference between the three HPN concentrations for the two cycling models. Thus, it can be concluded that HPN at concentrations of 0.1%, 0.5% and 1% was able to reduce erosion and abrasion wear, and at 1% concentration it reduced erosion wear, but its effect did not overcome EGCG.